Effect of welding current on the dimensions of bead in tungsten inert gas welding process. (2021) - Singh, Rudra Pratap; Agrawal, Manoj Kumar
Abstract: In our daily industrial life joints are very important. The industries are worthless without machines and the parts of machines are connected generally by joints. Welding is a popular method of making joints and the tungsten inert gas welding is a powerful method the welding process. The dimensions of the beads of welding are very important to decide the strength and hardness of the joints, which are the required properties of the weld. The dimensions of the weld bead are penetrated depth, width of weld and height of reinforcement which decides the mechanical properties of the weld. In this work the experiments were performed with Tungsten Inert Gas Welding process to analysis the impact of welding current on the dimensions of the bead. All the other input variables except the welding current were fixed, as the feed rate at 6.35 mm/s, voltage at 9.6 V, travel speed or welding speed at 1.44 mm/s for whole the experimentation period. Only the values of welding currents were varied and the effect of this variation on penetrated depth, width of weld and height of reinforcement were investigated. Total 6 pairs of mild steel test pieces of dimensions 75 mm × 50 mm × 5 mm were welded for 6 variations of welding current. The results were tabulated and were expressed in three different diagrams one for penetrated depth, one for height of reinforcement and one for width of weld. This study explains the sensitivity analysis of the effect of the welding current on the three dimensions of the weld bead.